Quality and outcomes of maternal and perinatal care for 76, 563 pregnancies reported in a nationwide network of Nigerian referral-level hospitals. (May 2022) - Tukur, Jamilu; Lavin, Tina; Adanikin, Abiodun; Abdussalam, Muhammed; Bankole, Kuti; Ekott, Mabel Ikpim; Godwin, Akaba; Ibrahim, Halima A; Ikechukwu, Okonkwo; Kadas, Saidu Abubakar; Nwokeji-Onwe, Linda; Nzeribe, Emily; et al.
Summary: Background: The WHO in collaboration with the Nigeria Federal Ministry of Health, established a nationwide electronic data platform across referral-level hospitals. We report the burden of maternal, foetal and neonatal complications and quality and outcomes of care during the first year. Methods: Data were analysed from 76, 563 women who were admitted for delivery or on account of complications within 42 days of delivery or termination of pregnancy from September 2019 to August 2020 across the 54 hospitals included in the Maternal and Perinatal Database for Quality, Equity and Dignity programme. Findings: Participating hospitals reported 69, 055 live births, 4, 498 stillbirths and 1, 090 early neonatal deaths. 44, 614 women (58·3%) had at least one pregnancy complication, out of which 6, 618 women (8·6%) met our criteria for potentially life-threatening complications, and 940 women (1·2%) died. Leading causes of maternal death were eclampsia ( n  = 187, 20·6%), postpartum haemorrhage (PPH) ( n  = 103, 11·4%), and sepsis ( n  = 99, 10·8%). Antepartum hypoxia ( n  = 1455, 31·1%) and acute intrapartum events ( n  = 913, 19·6%) were the leading causes of perinatal death. Predictors of maternal and perinatal death were similar: low maternal education, lack of antenatal care, referral from other facility, previous caesarean section, latent-phase labour admission, operative vaginal birth, non-use of a labour monitoring tool, no labour companion, and non-use of uterotonic for PPH prevention. Interpretation: This nationwide programme for routine data aggregation shows that maternal and perinatal mortality reduction strategies in Nigeria require a multisectoral approach. Several lives could be saved in the short term by addressing key predictors of death, including gaps in the coverage of internationally recommended interventions such as companionship in labour and use of labour monitoring tool. Funding: This work was funded by MSD for Mothers; and UNDP/UNFPA/ UNICEF/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction (HRP), a co-sponsored programme executed by the World Health Organization (WHO).